Comparative study between efficacy of magnesium sulphate and lignocaine in attenuating haemodynamic response to laryngoscopy and endotracheal intubation - Hossain, MPA; Islam, MS; Chowdhury, MH; Ahmed, M; Haque, M; Aleem, MA; Chowdhury, JP (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i1.13533 JAFMC Vol.8(1) 2012 pp.15-19